Comparison of Pectoral Nerve Block (II) And Erector Spinae Block for Postoperative Analgesia Following Breast Surgeries - Hameed, Umar; Rehman, Ali; Mohamin , Muhammad; Ali , Muhammad Qasim (Indus Journal of Bioscience Research, 2025)
Introduction: Effective postoperative pain management is essential in breast cancer surgeries to enhance recovery and reduce opioid-related side effects. Regional anesthesia techniques, such as the Pectoral Nerve Block (PECS-II) and Erector Spinae Plane (ESP) Block, have been used as opioid-sparing strategies. However, comparative data on their efficacy remain limited. This study aimed to evaluate and compare the analgesic effectiveness of PECS-II and ESP blocks in postoperative pain control, opioid consumption, and time to first analgesic requirement in patients undergoing breast surgery. Methodology: This randomized controlled study included 60 patients undergoing elective breast cancer surgery, divided into two groups: PECS-II (n=30) and ESP (n=30). Patients were randomly assigned using a computer-generated randomization method. Both blocks were performed under ultrasound guidance 30 minutes before general anesthesia. Postoperative pain was assessed using the Numeric Rating Scale (NRS) at multiple time intervals (immediately, 1, 2, 6, 12, and 24 hours). Primary outcomes included nalbuphine consumption, time to first analgesic requirement, and pain scores. Data were analyzed using SPSS, with p<0.05 considered statistically significant. Results: The PECS-II group had lower nalbuphine consumption (1.72 ± 3.24 mg vs. 3.79 ± 4.22 mg, p = 0.037) and a longer time to first analgesic (9.01 ± 1.68 vs. 4.64 ± 0.98 hours, p = 0.001). Pain scores at all-time intervals were significantly lower in the PECS-II group (p = 0.001), indicating superior and prolonged analgesia with reduced opioid use. Conclusion: The PECS-II block provided superior postoperative analgesia with lower pain scores, reduced opioid consumption, and prolonged analgesic duration compared to the ESP block. These findings support its preference for effective pain management in breast surgeries.